(3SdWGJ eCehQi GdVHW GdbVGFi GdeJYdbI HGdJMbjb GdGHJOGFi (B: s (3OQGSI Hjf GdbGfhf GdchjJi h GdeUQi (B/ s - (3eaQM eMeO GdeWjQis; (3TQja SjO cGed s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2016)
(3Ef deCehQ GdVHW GdbVGFi UdGMjGJ hab GdbGfhf(B: (3h Ef ef gPg GdUdGMjGJ eG gh efUhU Ydjg HTcd eHGTQ ai fUhU GdbGfhf h efgG eG gh efUhU Ydjg ai MGdGJ GSJKfGFjI(B: (3h bO JfGhdJ gPg GdQSGdI gPg GdUdGMjGJ GdGSJKfGFjI HMjK Je GdHMK ai gPg GdQSGdI Yf MGdGJ JhGaQ UhQ GdLQjeI GdeTghOI h gi GdLQjeI GdJi jMb deCehQ GdVHW GdbVGFi Cf jHGTQ CYeGd GdJMbjb ajgG(B: (3h Je HMK CjVkG ehVhY Jcdja eCehQ GdVHW GdbVGFi HCYeGd GdJMbjb ai LQjeI eMOOI ef bHd LgI GdGNJUGU h gi YGOI eG Jchf ai EWGQ eMOO hab GdJTQjYGJ GdELQGFjI dbhGfjf GdLRGAs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2016s
(3HHdjhLQGajG(B: (3UaMGJ (B394-417s
Keywords: (3GdbGfhf GdLfGFjs; (3fXGe GdVHWjI GdbVGFjI aj eUQs; (3GdJdHS s; (3eaghe GdVHW GdbVGFj s; (3GdfOH s; (3GdbHV Ydj GdeJgejfs; (3GdGdJRGe HGdbhGYO GdeJHYI aj GdJMbjb GdGHJOGFjs; (3JaJjT GdeJgejf heSGcfge s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs